EPEN-02. CLINICAL OUTCOME OF PEDIATRIC EPENDYMOMAS: A SINGLE INSTITUTION EXPERIENCE. Issue 2 (22nd June 2018) - Ohe, Naoyuki; Nishiwaki, Takayuki; Nakayama, Noriyuki; Yano, Hirohito; Iwama, Toru
Abstract: OBJECTIVE: The standard therapy for children with ependymoma consists of maximal surgical resection followed by focal irradiation, but chemotherapy has not a role in most treatment regimens for ependymoma to date. We evaluated the curative effects for the children with ependymoma in Gifu University Hospital. PATIENTS: Between 2002 and 2017, 9 children (6 boys and 3 girls) with median age of 6.8 years (range 2–18 years), 4 supratentorial ependymomas (WHO grade II: 3 cases, grade III: 1 case) and 5 infratentorial ependymomas (WHO grade II: 3 cases, grade III: 2 cases) were treated. Treatment protocol between 2002 and 2006, all children underwent surgery followed by focal irradiation and only children with WHO grade III ependymoma were done chemotherapy, between 2007 and 2013, all children underwent surgery followed by irradiation with/without chemotherapy. Recently, recurrent ependymoma patients underwent tumor removal followed by phoyodynamic therapy (PDT) using Talaporfin Sodium. RESULTS: Median progression-free survival (PFS) was 80 months. 5-year OS was 70% and 10-year OS was also 70%. The significant difference was not recognized in surgery, location, radiotherapy and chemotherapy. CONCLUSION: Maximal surgical resection and local radiotherapy are thought to be a standard therapy for the ependymoma. PDT for ependymoma have no evidence at present, but we want to accumulate cases.